Cure of peptic gastric ulcer associated with eradication of Helicobacter pylori. Finnish Gastric Ulcer Study Group. Issue 6 (June 1995) - Seppälä, K; Pikkarainen, P; Sipponen, P; Kivilaakso, E; Gormsen, M H
Abstract : The effect of Helicobacter pylori eradication on ulcer healing and the relapse rate were investigated in a multicentre trial of 239 gastric ulcer patients. Patients with H pylori positive gastric ulcer were randomly assigned to one of three groups: (A) 10 days' treatment with metronidazole and eight weeks' treatment with colloidal bismuth subcitrate (CBS) (84 patients); (B) 10 days' treatment with metronidazole placebo and eight weeks with CBS (73 patients); or (C) ranitidine (82 patients). At 12 weeks in 210 patients, gastric ulcer was present in three (9%) of 35 H pylori negative patients, and in 45 (26%) of 175 H pylori positive patients (p < 0.05). Results after one year of follow up were available for 205 patients. Between 12 and 52 weeks, two (7%) ulcer relapses occurred in 29 H pylori negative patients and in 60 (47%) of 128 H pylori positive patients (p < 0.001). After two weeks of open triple therapy (CBS 120 mg four times daily, amoxicillin 500 mg four times daily, and metronidazole 400 mg three times daily), given to the patients with ulcer relapse, only one (an NSAID user) of 55 successfully treated patients had an ulcer relapse during the one year follow up. Healing of gastric ulcer is rapid and recurrence is infrequent after successful H pylori eradication. H pylori eradication changes the natural history of the gastric ulcer disease.